Pecel Pithik: Tradition, Culture, and Its Impact on The Socioeconomic Welfare of Osingese People in Banyuwangi - Farida Wahyuningtyas; Akhmad Haryono; Novia Luthviatin; Ahmad Nafi'; Iken Nafikadini (Institut Agama Islam Negeri Madura, 2018)
This study aimed to explore and describe the existence of pecel pithik in the tradition of Osingese tribe of Banyuwangi and its impact on the social economic welfare of the very community. Qualitative approach method was used to achieve the purpose of this research. Data were collected through observation, in-depth interviews, note taking, and recording. Data analysis method operative in the study was descriptive qualitative method with thematic content analysis. This study has evinced that pecel pithik is a cultural asset of Osingese society, which is rooted in fundamental traditional agrarian values with selamatan, originally presented in rice fields in the form of tumpeng before harvest in the hope of good harvest and blessing. This was done to improve the society’s welfare and elevate their degree. Today, pecel pithik presented at rituals (selamatan) such as barong ider bumi and tumpeng sewu (bersih desa). Pecel Pithik has now been a potential of socioeconomic capital for regional progress as a resource of economic development to improve societies’ welfare.